The Rationale for Exercise in the Management of Pain in Parkinson’s Disease - Natalie E. Allen; Niamh Moloney; Vanessa van Vliet; Colleen G. Canning (2015)
Pain is a distressing non-motor symptom experienced by up to 85% of people with Parkinson’s disease (PD), yet it is often untreated. This pain is likely to be influenced by many factors, including the disease process, PD impairments as well as co-exi